Whittaker Chambers: A Biography - Schrecker, Ellen (Labour / Le Travail, 1998)
The article reviews the book, "Whittaker Chambers: A Biography," by Sam Tanenhaus.

Academic Freedom in Conflict: The Struggle Over Free Speech Rights in the University - Schrecker, Ellen (Labour / Le Travail, 2015)
The article reviews the book, "Academic Freedom in Conflict: The Struggle Over Free Speech Rights in the University," edited by James L. Turk.